Use of Circumferentially Cracked Bar sample for CTOD fracture toughness determination in the upper shelf regime - D. Gentile; I. Persechino; N. Bonora; G. Iannitti; A. Carlucci (Fracture and Structural Integrity)
In this work, the use of circumferentially cracked bar (CCB) sample to determine material fracture toughness in the upper shelf regime for carbon steels has been investigated. Since high fracture toughness materials are known to exhibit extensive crack tip blunting before ductile crack initiation, accurate specimen design is required to provide realistic fracture toughness measurement. Here, a CCB was designed to have similar loss of constraint as for SENT sample. Continuum damage mechanics was used to predict the occurrence of ductile crack initiation and propagation. Finite element analysis was performed to predict specimen response and to compare computed J-integral crack driving force with measured CTOD. Finally, experimental tests were performed on X65 carbon steel and the measured critical CTOD was compared with available fracture data obtained with SENT.